Estrogen Receptor Beta (ERβ): A Ligand Activated Tumor Suppressor - Mal, Rahul; Magner, Alexa; David, Joel; Datta, Jharna; Vallabhaneni, Meghna; Kassem, Mahmoud; Manouchehri, Jasmine; Willingham, Natalie; Stover, Daniel; Vandeusen, Jeffery; Sardesai, Sagar; Williams, Nicole; et al. (Frontiers in Oncology, 2020)
Estrogen receptor alpha (ERα) and estrogen receptor beta (ERβ) belong to a superfamily of nuclear receptors called steroid hormone receptors, which, upon binding ligand, dimerize and translocate to the nucleus where they activate or repress the transcription of a large number of genes, thus modulating critical physiologic processes. ERβ has multiple isoforms that show differing association with prognosis. Expression levels of the full length ERβ1 isoform are often lower in aggressive cancers as compared to normal tissue. High ERβ1 expression is associated with improved overall survival in women with breast cancer. The promise of ERβ activation, as a potential targeted therapy, is based on concurrent activation of multiple tumor suppressor pathways with few side effects compared to chemotherapy. Thus, ERβ is a nuclear receptor with broad-spectrum tumor suppressor activity, which could serve as a potential treatment target in a variety of human cancers including breast cancer. Further development of highly selective agonists that lack ERα agonist activity, will be necessary to fully harness the potential of ERβ.